The Language Game as the Constitutive Component of Postmodern Plurality with Regard to Moral and Intellectual Preferences of Contemporary Society - Zilova, Zuzana (Communications - Scientific letters of the University of Zilina, 2010)
The contribution deals with the analysis of postmodern plurality by applying the term a “language game” to the postmodern condition. It makes use of the word that originally derives from Wittgenstein’s analytic philosophy and was supplemented with Lyotard’s conception that sees the society as the multi–central body consisting of many independent areas. It tries to emphasise the advantages of the situation such as freedom of expressions, wide range of options to choose from, creativity, but faces up disorganization. It examines the possibility of development and the role of knowledge in the situation of plurality.